Diseño de un Sistema de Adquisición de Datos para procedimientos de almacenamiento de combustible en la empresa Petrocomercial Terminal Ambato - Ureña Aguirre, Jeanette del Pilar (2011)
This project entitled "Design of a Data Acquisition System for storage procedures in fuel tanks in the Pe Company"Terminal Ambato" includes an automatic system for measuring level of tanks by means of two types of radars for floating roof (floatroof) and for fixed roof (fixedroof).The Ambato Terminal has 8 tanks, the same ones that will store products as Extra, Diesel 2 and Super; which will be corrected at 6o®F and 14.69 Psi. for an adeevery measurement of product level - water, temperature, density and volume.The project itself is divided into two parts: HARDWARE AND SOFTWARE, the first inincludes a Detailed Engineering where all the equipment, piping, wiring, accessories and others, while in Software the configuration is establishedtion of the different radar heads and complementary equipment, in addition to present an Application in Intouch for monitoring, alarms and histories of the variables mentioned above both in general and independentlyslope for each of the tanks.The System Design has all the Safety standards required for work in classified areas.